Ab initio description of oxygen vacancies in epitaxially strained $$\hbox {SrTiO}_{{3}}$$ SrTiO 3 at finite temperatures - Zizhen Zhou (Nature Portfolio, 2021)
Abstract Epitaxially grown $$\hbox {SrTiO}_{{3}}$$ SrTiO 3 (STO) thin films are material enablers for a number of critical energy-conversion and information-storage technologies like electrochemical electrode coatings, solid oxide fuel cells and random access memories. Oxygen vacancies ( $${V_{O}}$$ V O ), on the other hand, are key defects to understand and tailor many of the unique functionalities realized in oxide perovskite thin films. Here, we present a comprehensive and technically sound ab initio description of $${V_{O}}$$ V O in epitaxially strained (001) STO thin films. The novelty of our first-principles study lies in the incorporation of lattice thermal excitations on the formation energy and diffusion properties of $${V_{O}}$$ V O over wide epitaxial strain conditions ( $$-4 \le η \le +4$$ - 4 ≤ η ≤ + 4 %). We found that thermal lattice excitations are necessary to obtain a satisfactory agreement between first-principles calculations and the available experimental data for the formation energy of $${V_{O}}$$ V O . Furthermore, it is shown that thermal lattice excitations noticeably affect the energy barriers for oxygen ion diffusion, which strongly depend on $$η $$ η and are significantly reduced (increased) under tensile (compressive) strain. The present work demonstrates that for a realistic theoretical description of oxygen vacancies in STO thin films is necessary to consider lattice thermal excitations, thus going beyond standard zero-temperature ab initio approaches.